The role of surgery in advanced thymic tumors: A retrospective cohort study - Qi, Weifeng; Tian, Hui (Frontiers in Oncology, 2023)
Background: There is no definite and detailed treatment guideline for advanced thymic tumors which means the presence of lymph nodes and other organs metastasis, and clinical guidelines recommend chemotherapy-based multidisciplinary treatment. Previous studies found that surgery played a beneficial effect on advanced thymic tumors, but because of few cases with advanced thymic tumors and incomplete studies, the role of surgery is still unknown. Therefore, this paper aims to systematically analyze the role of surgery in advanced thymic tumors based on the Surveillance, Epidemiology, and End Results (SEER) database with a sufficient number of cases. The significance of this study is to clarify the prognostic value of surgery in advanced thymic tumors. Method: The total number of 979 patients with advanced thymoma or advanced thymic carcinoma were collected from the Surveillance, Epidemiology, and End Results (SEER) database. The propensity score matching was performed to eliminate confounding factors, and Cox regression analyses were executed to assess prognosis. Results: This study put all patients into four groups according to pathology and surgery or not: Thymoma (Surgery), Thymoma (No Surgery), Thymic carcinoma (Surgery), and Thymic carcinoma (No Surgery). Before and after propensity score matching, disease-specific survival was significantly different between advanced thymoma(surgery) and advanced thymoma (no surgery) (p< 0.001 and p<0.001); Similarly, disease-specific survival was significantly different between advanced thymic carcinoma(surgery) and advanced thymic carcinoma (no surgery) (p< 0.001 and p=0.003). The no total resection, distant metastasis, and thymic carcinoma were all unfavorable prognostic factors. Conclusions: This study proved that whether in advanced thymoma or advanced thymic carcinoma, surgery played a positive role which significantly improved survival time. Meanwhile, the total resection of the primary site was better. This study would also provide a reference for the clinical treatment of advanced thymic tumors.